Encapsulated 3Ø converter for power loss minimization in a grid-connected system - Suresh K; Parimalasundar E; Jayakumar S; Ravikumar R (Automatika, 2023)
ABSTRACTA newly designed DC–AC three phase bidirectional converter (DATBC) with an encapsulated DC–DC converter (EDC) for the energy storage system (ESD) is analysed and investigated in this research paper. By using encapsulated or embedded or hidden DC–DC converter a stable and constant DC bus is developed between the encapsulated DC–DC converter and DC–AC three phase bidirectional converter. The proposed converter is entirely different from the traditional dual-stage DC–AC converter, because it takes less than 20% of power used for the DC–AC conversion process. So, this reduced power consumption increases efficiency to a considerable value. A new control technique for zero sequence has been adopted components are inserted in the modulating signal based on carrier pulse width modulation (CPWM). Working principle, implementation and characteristics of the DC–AC three phase bidirectional converter are analysed. Effectiveness and feasibility of the developed converter are examined with a proto-type model.